2021
DOI: 10.3389/fpls.2021.675121
|View full text |Cite
|
Sign up to set email alerts
|

Runoff Losses in Nitrogen and Phosphorus From Paddy and Maize Cropping Systems: A Field Study in Dongjiang Basin, South China

Abstract: Graphical AbstractThe experimental location and setup details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…It indicated that Chinese farmers should put less than 120 kg ha -1 N fertilizer application to avoid benefit lost during alfalfa production. Moreover, the high N input also enhances losses through leaching, volatilization and denitrification ( Barker and Culman, 2020 ; Zeng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that Chinese farmers should put less than 120 kg ha -1 N fertilizer application to avoid benefit lost during alfalfa production. Moreover, the high N input also enhances losses through leaching, volatilization and denitrification ( Barker and Culman, 2020 ; Zeng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…And this area is a densely populated and intensively farm region with a high cropping index (i.e., the average number of annual crop seasons). The experimental soil used was acid red soil, with a depth of 0 cm to 60 cm, which is a typical soil type in South China ( Zeng et al., 2021 ). The topsoil had the following physicochemical characteristics: bulk density of 1.26 g·cm -3 , soil pH of 5.83, soil organic matter of 15.49 g·kg -1 , total phosphorus of 0.16 g·kg -1 , and total nitrogen (TN) of 1.05 g·kg -1 , with alkali-hydrolyzed nitrogen of 35.16 g·kg -1 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, runoff and leaching are the main processes of nitrogen loss ( Chen et al., 2022 ). Currently, numerous studies have examined nitrogen runoff loss in paddy fields of South China ( Ding et al., 2016 ; Issaka et al., 2019 ; Zeng et al., 2021 ). In our previous study, we found a 31.7% reduction in nitrogen loss from paddy field runoff in the SWI groups compared to that in the traditional irrigation (TI) groups ( Zeng et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the nutrients in the slope soil are lost with runoff via dissolution in surface water, while some are lost with sediment via adsorption in soil particles (Zeng et al, 2021). When the wind direction was constant, the loss of different forms of N and P along with runoff and sediment increased with rainfall intensity, indicating that there was a synergistic interaction between rainfall intensity and nutrient loss.…”
Section: N and P Lossmentioning
confidence: 99%